2014
DOI: 10.1111/jgh.12797
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gastric cancer diagnosis using new ultrathin transnasal endoscopy with narrow‐band imaging: Preliminary study

Abstract: Background and Aim: The new developed ultrathin transnasal endoscope, the GIF-XP290N, makes possible a resolving power similar to the GIF-H260 at a distance of 3 mm. In this study, using the GIF-XP290N, we evaluated whether endoscopic diagnosis (discrimination between benign and malignant) of gastric lesions is possible using nonmagnified narrow-band imaging (NBI) endoscopy. Methods: The subjects were 255 consecutive patients who underwent screening of the gastrointestinal tract using new ultrathin transnasal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Pimentel-Nunes et al proposed diagnostic criteria to characterise gastric premalignant lesions including chronic gastritis, IM and carcinoma using non-magnifying NBI,96 and these criteria were validated in a multicentre prospective cohort study 37. One observational study indicated that diagnostic accuracy for differentiating adenocarcinoma from benign gastric lesions was significantly higher in non-magnification NBI than in WLE (92.3% vs 61.5%) 97. At present, the consensus panel recommended the use of equipment-based IEE without magnification for characterisation and delineation of EGC as evidenced by the accuracy of IEE without magnification demonstrated in prospective cohort studies 96 97…”
Section: Consensus Statementsmentioning
confidence: 99%
“…Pimentel-Nunes et al proposed diagnostic criteria to characterise gastric premalignant lesions including chronic gastritis, IM and carcinoma using non-magnifying NBI,96 and these criteria were validated in a multicentre prospective cohort study 37. One observational study indicated that diagnostic accuracy for differentiating adenocarcinoma from benign gastric lesions was significantly higher in non-magnification NBI than in WLE (92.3% vs 61.5%) 97. At present, the consensus panel recommended the use of equipment-based IEE without magnification for characterisation and delineation of EGC as evidenced by the accuracy of IEE without magnification demonstrated in prospective cohort studies 96 97…”
Section: Consensus Statementsmentioning
confidence: 99%
“…The data from five case-control studies and two cohort studies in Japan demonstrated that photofluoroscopy for gastric cancer screening can decrease gastric cancer mortality by 40-60% [12]. By now, many new advanced approaches providing better visualization of gastric mucosa lesions have been developed, such as chromoendoscopy [62], confocal laser endomicroscopy [63], narrow-band imaging endoscopy [64], magnifying endoscopy [65] and narrow-band imaging with magnifying endoscopy [66]. A large number of studies showed that these new advanced endoscopic imaging technologies have better accuracy for diagnosing premalignant gastric lesions than standard ‘white light' endoscopy [67,68,69].…”
Section: Prevention Strategies For Gastric Cancermentioning
confidence: 99%
“…In the present study, we demonstrated the clinical utility of M-TNE in patients with dysphagia. TNE is becoming popular worldwide, particularly for cancer screening (13). Using a trans-nasal endoscope, the catheter can be inserted under direct vision, resulting in smooth and safe insertion.…”
Section: Discussionmentioning
confidence: 99%